Multidrug resistant 1 (MDR1) C3435T and G2677T gene polymorphism: impact on the risk of acute rejection in pediatric kidney transplant recipients - Mai S Korkor; Tarek el-desoky; Youssef M Mosaad; Doaa M. Salah; Ayman Hammad (BMC, 2023)
Abstract Background Tacrolimus is the backbone drug in kidney transplantation. Single nucleotide polymorphism of Multidrug resistant 1 gene can affect tacrolimus metabolism consequently it can affect tacrolimus trough level and incidence of acute rejection. The aim of this study is to investigate the impact of Multidrug resistant 1 gene, C3435T and G2677T Single nucleotide polymorphisms on tacrolimus pharmacokinetics and on the risk of acute rejection in pediatric kidney transplant recipients. Methods Typing of Multidrug resistant 1 gene, C3435T and G2677T gene polymorphism was done using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) for 83 pediatric kidney transplant recipients and 80 matched healthy controls. Results In Multidrug resistant 1 gene (C3435T), CC, CT genotypes and C allele were significantly associated with risk of acute rejection when compared to none acute rejection group (P = 0.008, 0.001 and 0.01 respectively). The required tacrolimus doses to achieve trough level were significantly higher among CC than CT than TT genotypes through the 1st 6 months after kidney transplantation. While, in Multidrug resistant 1 gene (G2677T), GT, TT genotypes and T allele were associated with acute rejection when compared to none acute rejection (P = 0.023, 0.033 and 0.028 respectively). The required tacrolimus doses to achieve trough level were significantly higher among TT than GT than GG genotypes through the 1st 6 months after kidney transplantation. Conclusion The C allele, CC and CT genotypes of Multidrug resistant 1 gene (C3435T) and the T allele, GT and TT genotypes of Multidrug resistant 1 gene (G2677T) gene polymorphism may be risk factors for acute rejection and this can be attributed to their effect on tacrolimus pharmacokinetics. Tacrolimus therapy may be tailored according to the recipient genotype for better outcome.